2015
DOI: 10.1016/j.pcad.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of Fitness in the Metabolically Healthy but Obese Phenotype: A Review and Update

Abstract: Despite the strong and consistent evidence supporting that a high physical fitness (PF) level at any age is a major predictor of a healthier metabolic profile, major studies focused on the metabolically healthy but obese (MHO) phenotype have ignored the role of PF when examining this phenotype and its prognosis. Particularly, the role of its main health-related components such as higher cardiorespiratory fitness (CRF) and muscular fitness in the MHO phenotype needs to be reviewed in depth. The present review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 46 publications
(25 reference statements)
5
60
0
3
Order By: Relevance
“…In 2014, Blüher and Schwarz 100 reviewed and updated the characterization of the MHO individuals and concluded . Based on this definition and using term/abbreviations already used in the literature, this group could be named as MAO 65,66,104,105,[153][154][155] or MUHO. 75,94,101,111,117,156 This definition would be problematic from both a clinical and analytic point of view, how would be considered/ treated those individuals who meet only 1 criteria and are therefore left out from the MHO group and also from the MAO/MUHO group?…”
Section: Characteristics Of Mho Individualsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, Blüher and Schwarz 100 reviewed and updated the characterization of the MHO individuals and concluded . Based on this definition and using term/abbreviations already used in the literature, this group could be named as MAO 65,66,104,105,[153][154][155] or MUHO. 75,94,101,111,117,156 This definition would be problematic from both a clinical and analytic point of view, how would be considered/ treated those individuals who meet only 1 criteria and are therefore left out from the MHO group and also from the MAO/MUHO group?…”
Section: Characteristics Of Mho Individualsmentioning
confidence: 99%
“…Recent reviews on this topic concluded that most of previous studies focused on MHO used definitions based on MetS criteria. 104,111 In addition, the markers of insulin resistance/sensitivity normally used are more costly than the markers included in the MetS definition, which reduces the feasibility and potential usefulness of the MHO in clinical and other settings. This is also the reason why fasting glucose is used for the MetS definition, instead of more expensive measures such as fasting insulin (or indexes derived from it, eg, homeostatic model assessment or quantitative insulin sensitivity check index) or the gold standard diagnostic test, the hyperinsulinemic euglycemic glucose clamp.…”
mentioning
confidence: 99%
“…Date of birth was used to calculate age, and postcode was used to determine area-level deprivation using the English Indices of Deprivation (EID) 20 .…”
Section: Demographic and Anthropometric Measurementsmentioning
confidence: 99%
“…Based on these findings, Roberson and colleagues 12 suggested that all studies examining the MHO phenotype should assess physical activity or fitness due to their possible mediating effect on cardiovascular disease risk. Another recent review characterizing the role of fitness in the MHO phenotype identified ten studies reporting higher fitness in MHO compared with MUO phenotypes (Ortega et al, 2015). Findings were mostly limited to comparisons between small groups of post-menopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Observaron también que, para una capacidad aeróbica dada, este grupo tenía un mejor pronóstico futuro que el resto de obesos y similar a personas con normopeso metabólicamente sanas (193). Una revisión en profundidad de la literatura existente en esta temática (195) concluye que hasta la fecha, solo un estudio ha explorado si estas diferencias en capacidad aeróbica observadas en población adulta existen también en adolescentes (n = 108) (196). Los autores observaron una mayor capacidad aeróbica en adolescentes obesos metabólicamente sanos que en el resto de compañeros obesos (consumo máximo de oxígeno = 44,0 vs. 42,7 ml/kg/min, respectivamente), aunque estas diferencias no fueron significativas.…”
Section: Niños Con Sobrepeso/obesidad Pero En Forma (Fat But Fit)unclassified